Risk Factors of Gastrointestinal Bleeding in Patients Receiving New Oral Anticoagulants - Ju Yup Lee (Yong Chan Lee, 2018)
New oral anticoagulants (NOACs) are now widely used for the prevention and treatment of venous thrombosis, and for the prevention of stroke and systemic embolism in patients with atrial fibrillation. As compared with warfarin, NOACs have the advantage of rapid onset of action and less drug interaction. However, they carry a higher risk of gastrointestinal (GI) bleeding than warfarin. The risk of GI bleeding in patients using NOACs varies according to the type and dose of the drug. By contrast, apixaban and edoxaban are reported to carry similar risks as warfarin, and the risks with dabigatran and rivaroxaban are higher than that with warfarin. In patients using NOACs, old age, impaired renal function, impaired liver function, concurrent use of antiplatelet agents, and non-steroidal anti-inflammatory drugs are considered major risk factors of GI bleeding, and gastroprotective agents such as histamine-2 receptor antagonist and proton pump inhibitor have preventive effects. To prevent GI bleeding associated with NOACs, the characteristics of each NOAC and the risk factors of bleeding should be recognized.